The economic case for prioritizing governance over financial incentives in REDD+ - Fosci, Mattia (Taylor and Francis, 2013)
This article contributes to the ongoing debate on the role of public policies and financial incentives in Reducing Emissions from Deforestation and forest Degradation (REDD+). It argues that the subordination of policies to results-based payments for emission reductions causes severe economic inefficiencies affecting the opportunity cost, transaction cost and economic rent of the programme. Such problems can be addressed by establishing sound procedural, land and financial governance at the national level, before REDD+ economic incentives are delivered at scale. Consideration is given to each governance dimension, the entry points for policy intervention and the impact on costs. International support must consider the financial and political cost of governance reforms, and use a pay-for-results ethos based on output and outcome indicators. This can be done in the readiness process but only if the latter’s legal force, scope, magnitude and time horizon are adequately reconsidered. In sum, the paper provides ammunition for the institutionalist argument that UNFCCC Parties must prioritise governance reform between now and the entry into force of the new climate agreement in 2020, and specific recommendations about how this can be done: only by doing so will they create the basis for the programme’s financial sustainability.